Financial Performance Analysis of PT Bank Perkreditan Rakyat - Yunita Pakpahan; Verawati Br Karo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The end of the COVID-19 pandemic has brought significant changes to the banking world in achieving banking financial performance because this is closely related to the sustainability of businesses managed by customers. To see bank performance, it is necessary to analyze financial performance for the past, current, and future periods. This research aims to determine the financial condition based on liquidity ratios, solvency ratios, and profitability ratios at PT. Bank Rakyat Nusantara Bonapasogit 15 (BPR NBP 15) credit period 2020-2022. Field research method with a direct approach to the company that is the object of research. The results of this research explain the liquidity ratio, solvency ratio, and profitability ratio at PT. Bank Rakyat Nusantara Bonapasogit 15 (BPR NBP 15) credit for the 2020-2022 period is in a good category.